The Evaluation of Serum Surfactant Protein D (SP-D) Levels as a Biomarker of Lung Injury in Tuberculosis and Different Lung Diseases - Güzel, A.; Karadaǧ, A.; Okuyucu, A.; Alaçam, H.; Küçük, Y. (Verlag Klinisches Labor GmbH Cecile.Leugner@clin-lab-publications.com, 2014)
Background: To evaluate the predictive powers of serum surfactant protein D (SP-D) levels as a biomarker of lung damage in tuberculosis and lung diseases. Methods: This study prospectively included 137 subjects who applied to our hospital. We measured serum SP-D levels from patients with active tuberculosis (TB) (n = 35), chronic obstructive disease (COPD) patients experiencing acute exacerbations (n = 30), patients with pneumonia (n = 45), and control subjects (n = 27). Results: The mean age of all patients was 54.89 ± 18.81 years (15 to 100 years); males accounted for two-thirds (70.1%) of the cases. Serum SP-D levels were higher in patients with pnemonia, tuberculosis, and COPD than in control patients (p < 0.001, p < 0.001, and p < 0.001, respectively). Serum SP-D levels in patients with pneumonia, tuberculosis, and COPD were higher than in the control group and mean serum SP-D levels were associated with pulmonary injury scores in patients with pneumonia, severity of COPD attack, and the extent of radiological lung involvement in patients with pneumonia and TB. Conclusions: Serum SP-D may be a useful biomarker of the severity of pneumonia, COPD, and tuberculosis.
Keywords: Biomarkers; COPD; Pneumonia; Protein D; Surfactant; Tuberculosis